ONCE AGAIN ABOUT BETA-ADRENOBLOCKERS IN ARTERIAL HYPERTENSION. WHAT SHOULD DOCTOR RECOMMEND TO THE PATIENT? - S. Y. Martsevich (Рациональная фармакотерапия в кардиологии)
The role of beta-blockers (BB) in arterial hypertension therapy is discussed from the evidence based medicine point of view and according to international guidelines. Data of the latest meta-analysis comparing effects of BB and other antihypertensive drugs on a probability of cardio-vascular complications are presented.